The Epidemiology of Functional Gastrointestinal Disorders in Mexico: A Population-Based Study - Aurelio López-Colombo; Douglas Morgan; Dalia Bravo-González; Alvaro Montiel-Jarquín; Socorro Méndez-Martínez; Max Schmulson (Gastroenterology Research and Practice)
Aims. The frequency of functional gastrointestinal disorders (FGIDs) in the general population of Mexico is unknown. Methods. To determine the prevalence of FGIDs, associated depression, and health care utilization, a population-based sampling strategy was used to select 500 households in the State of Tlaxcala, in central Mexico. Household interviews were conducted by two trained physicians using the Rome II Modular Questionnaire, a health-care and medication used questionnaire and the CES-D depression scale. Results. The most common FGIDs were IBS: 16.0% (95% CI: 12.9–19.5); functional bloating: 10.8% (8.2–13.9); unspecified functional bowel disorder: 10.6% (8.0–13.6); and functional constipation (FC): 7.4% (5.3–10.1). Uninvestigated heartburn was common: 19.6% (16.2–23.4). All FGIDs were equally prevalent among both genders, except for IBS (P=0.001), IBS-C (P<0.001), IBS-A/M (P=0.049), and FC (P=0.039) which were more frequent in women. Subjects with FGIDs reported higher frequencies of medical visits: 34.6 versus 16.8%; use of medications: 40.7 versus 21.6%; (both P<0.001); and reported depression: 26.7 versus 6.7%, (P<0.001). Conclusion. In this first population-based study of FGIDs in Mexico, heartburn, IBS, functional distension, and FC were common. Only IBS, IBS-C, IBS-A/M, and FC were more frequent in women. Finally, FGIDs in Mexico had an increased burden of health care utilization and depression.